Phenotype and genotype variability of interspecific rice lines related to bacterial leaf blight resistance (Xanthomonas oryzae pv. oryzae) character (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Yuriyah S, Darnaedi D, Setia TM, Windarsih G, Utami DW. 2021. Phenotype and genotype variability of interspecific rice lines related to bacterial leaf blight resistance (Xanthomonas oryzae pv. oryzae) character. Biodiversitas 22: 4123-4130. Wild rice species are the source of the gene pool for rice genetic diversity. The cross-species crosses (interspecific crosses) play an important role in breeding, namely in terms of expanding the diversity of desirable characters, such as disease resistance and improvement in yield potential. Currently, the genes from wild rice species have been successfully introgressed into cultivated rice so that they can overcome the rice production constraints, including the introgression of genes for the bacterial leaf blight (BLB) resistance. The purpose of this study was to analyze the variability of phenotype and genotype performance of lines derived from wild rice species for the character of resistance to BLB disease. A total of 33 selected backcross lines derived from wild rice species of O. rufipogon and O. glaberrima as the donor parents and 2 control varieties (resistant and susceptible to BLB disease), were used in this study. The evaluation of phenotype and genotype of resistance characters to BLB disease was carried out during a vegetative phase of the plant. The resistance evaluation was carried out in a greenhouse, while the genotype performance was analyzed using 4 STS markers linked to Xa4, Xa7, and Xa13 genes. The result of the phenotype evaluation showed that there were variations among the resistance of the tested lines. Three lines derived from a Situ Bagendit/Oryza rufipogon cross were resistant to all BLB races used in the testing. Those three lines indicated to have the allele of the Xa7 resistance gene based on the genotype performance which grouped with the Code variety that had the Xa7 resistance gene.
Keywords: BLB resistance, molecular markers selection, wild rice species